2018
DOI: 10.21873/anticanres.12252
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Transumbilical Incision as an Approach for Organ Removal in Laparoscopy-assisted Colectomy

Abstract: Abstract. Aim: To investigate the risk factors of transumbilical incision for organ removal in laparoscopyassisted colectomy (LAC).In laparoscopic surgery, a transumbilical incision is often used for anastomosis and organ removal. In our Department, we have been performing transumbilical incisions to remove resected organs since shortly after the introduction of laparoscopic surgery. We vertically extend the umbilical wound corresponding to the size of the specimen and anastomose extracorporeally. We have alre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The incidence rate of SSI correlated with transumbilical incision in laparoscopic gastric and colorectal resections were low at 2.64% (4) and those in laparoscopic colectomy were at 4.31% (5). Meanwhile, SSI was not observed in patients who underwent laparoscopic hepatectomy (6) and LP in the current study.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…The incidence rate of SSI correlated with transumbilical incision in laparoscopic gastric and colorectal resections were low at 2.64% (4) and those in laparoscopic colectomy were at 4.31% (5). Meanwhile, SSI was not observed in patients who underwent laparoscopic hepatectomy (6) and LP in the current study.…”
Section: Discussionmentioning
confidence: 44%
“…The results showed that the incidence rate of SSIs and incisional hernias correlated with transumbilical incision were significantly higher in colorectal than in gastric resection in laparoscopic surgery. Moreover, female sex and diabetes mellitus (DM) were considered the independent risk factors for hernia formation, and SSI was not associated with hernia formation (4,5). In addition, a high body mass index (BMI) has been shown to be significantly associated with a greater risk of incisional hernia formation in laparoscopic hepatectomy (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning incisional hernia, the incidence rates of a portsite hernia have been reported to be 0%-25.9% (3). Furthermore, female sex, DM, SSI, wound size, and high BMI have been identified as risk factors for hernia formation (3,18). The surgical procedure was limited to Lap-H, and the incidence of hernia has been reported to be 1.85-5.9% (17,19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Adding an incision in the umbilicus has been avoided due to fear of increased rates of surgical site infection (SSI) and postoperative adhesion decades ago; however, it was not associated with complications (2). Furthermore, we have already reported the usefulness of a transumbilical incision as a surgical approach in laparoscopic surgery; infection at the transumbilical wound and incisional hernia occurred at a significantly higher rate following colorectal resection than gastric resection by laparoscopic surgery, and that female sex and diabetes mellitus (DM) were independent risk factors for hernia formation (3,4).…”
mentioning
confidence: 99%